2011
DOI: 10.1182/blood-2010-09-306357
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factors in human pulmonary arterial hypertension: a link to the intrinsic myeloid abnormalities

Abstract: Pulmonary arterial hypertension (PAH) is a proliferative vasculopathy characterized by high circulating CD34 ؉ CD133 ؉ proangiogenic progenitors, and endothelial cells that have pathologic expression of hypoxia-inducible factor 1 ␣ (HIF-1␣). Here, CD34 ؉ CD133 ؉ progenitor cell numbers are shown to be higher in PAH bone marrow, blood, and pulmonary arteries than in healthy controls. The HIF-inducible myeloid-activating factors erythropoietin, stem cell factor (SCF), and hepatocyte growth factor (HGF) are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
131
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(141 citation statements)
references
References 53 publications
6
131
2
2
Order By: Relevance
“…In the present study, we found a strong expression of HGF in PLs, consistent with the studies on human PAH (Farha et al, 2011). As an important factor responsible for vascular repair, HGF has been shown to enhance EPC function and improve EPC transplant efficiency in experimentally induced arterial injury (Song et al, 2009;Yu et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found a strong expression of HGF in PLs, consistent with the studies on human PAH (Farha et al, 2011). As an important factor responsible for vascular repair, HGF has been shown to enhance EPC function and improve EPC transplant efficiency in experimentally induced arterial injury (Song et al, 2009;Yu et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…However, as in healthy controls, there is a negative correlation between the two that is consistent with a reduction in hepcidin production as erythropoietic demand for iron increases [5,55]. Iron deficiency or anaemia may also drive increases in other HIF-inducible factors, including the myeloidactivating factors stromal-derived factor-1a, stem cell factor and hepatocyte growth factor [55].…”
Section: Regulation Of Iron Homeostasis In Ipahmentioning
confidence: 76%
“…Iron deficiency or anaemia may also drive increases in other HIF-inducible factors, including the myeloidactivating factors stromal-derived factor-1a, stem cell factor and hepatocyte growth factor [55]. This might contribute to myeloproliferative processes and recruitment of pro-angiogenic progenitor (CD34+ CD133+) cells to the pulmonary vasculature in PAH patients [55]. Interestingly, myeloid abnormalities were also demonstrated in unaffected relations of HPAH patients, suggesting that HIF-inducible factors and myeloid abnormalities may have a role in the pathology of PAH prior to the clinical manifestation of the disease.…”
Section: Regulation Of Iron Homeostasis In Ipahmentioning
confidence: 99%
“…Several independent investigations have described a mobilization of BM-derived cells during pulmonary hypertension. 2 Not only cells expressing c-kit are mobilized from BM in the circulation in response to hypoxia, but they are also found in the remodeled lung vessel wall in PAH (Figure 3 and Hayashida et al, 7 Davie et al, 8 Farha et al, 12 Spees et al, 24 and Sata et al 31 ). Activation of c-kit was reported as necessary for mobilization of reparative BM progenitor cells 32 and for the remodeling of blood vessels from these progenitor cells.…”
Section: Discussionmentioning
confidence: 98%
“…9 Other observations have also identified an association between PAH and BMrelated hematologic disorders 10 : in proliferative disorders of the hematopoietic stem cells such as myeloproliferative cancers, there is an unexplained high incidence of PAH. PAH is now a recognized complication of BM transplantation for leukemia, 11 chronic myeloproliferative disorders, 12 or in the treatment of malignant infantile osteopetrosis. 13 On the other hand, serotonin (5-hydroxytryptamine ) is associated with the pathogenesis of PAH.…”
Section: Introductionmentioning
confidence: 99%